2020
DOI: 10.48550/arxiv.2012.03908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Action-based distribution function modelling for constraining the shape of the Galactic dark matter halo

Kohei Hattori,
Monica Valluri,
Eugene Vasiliev

Abstract: We estimate the 3D density profile of the Galactic dark matter (DM) halo within π‘Ÿ 30 kpc from the Galactic centre by using the astrometric data for halo RR Lyrae stars from Gaia DR2. We model both the stellar halo distribution function and the Galactic potential, fully taking into account the survey selection function, the observational errors, and the missing line-of-sight velocity data for RR Lyrae stars. With a Bayesian MCMC method, we infer the model parameters, including the density flattening of the DM … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 80 publications
(145 reference statements)
1
23
0
Order By: Relevance
“…The errors are randomly generated from independent Gaussian distributions on each quantity for each star particle with standard deviations determined by characteristic or expected errors for Gaia and DESI observations. The Gaia heliocentric distance error is the same for all star particles at = 0.1107 (Hattori et al 2020). The Gaia proper motion errors ( * , ) are a function of 2 Gaia Expected Science Performance https://www.cosmos.esa.int/ web/gaia/science-performance -and also by Eq.…”
Section: Adding Observationally Motivated Selection Functions and Errorsmentioning
confidence: 98%
“…The errors are randomly generated from independent Gaussian distributions on each quantity for each star particle with standard deviations determined by characteristic or expected errors for Gaia and DESI observations. The Gaia heliocentric distance error is the same for all star particles at = 0.1107 (Hattori et al 2020). The Gaia proper motion errors ( * , ) are a function of 2 Gaia Expected Science Performance https://www.cosmos.esa.int/ web/gaia/science-performance -and also by Eq.…”
Section: Adding Observationally Motivated Selection Functions and Errorsmentioning
confidence: 98%
“…Gaia Collaboration et al 2018b;Antoja et al 2020;Gaia Collaboration et al 2021d), the Galactic potential (e.g. Crosta et al 2020;Cunningham et al 2020;Hattori et al 2020), and even the Hubble constant (e.g. Breuval et al 2020;Riess et al 2021;Baumgardt & Vasiliev 2021) are constantly increasing thanks to Gaia.…”
Section: Introductionmentioning
confidence: 99%
“…The mass distribution in different components of the Galaxy is of great importance to studies of the composition, history, and current dynamical properties of the Galaxy (e.g., Bland-Hawthorn & Gerhard 2016). Stellar streams in the halo have been extensively used to constrain the potential and the density distribution of the Galactic halo (e.g., Malhan & Ibata 2019;Hattori et al 2020;Reino et al 2020). Recent work has shown that the tidal tails of Hyades are likely sensitive to the exact prescription for the Galactic potential and the presence of GMCs (Jerabkova et al 2021).…”
Section: The Impact Of Gmcsmentioning
confidence: 99%